Availability of floral resources in yellow passion fruit cultivars - Oliveira Cobra, Simone Santos; Silva, Celice Alexandre; Krause, Willian; Lage, Laís (Federal University of Piauí, 2018)
The reproductive strategies and resources available in the flower are characteristics that stimulate research studies on the genetic improvement and fruit yield of commercial cultivars. In this sense, this study aimed to study the floral biology aspects of passion fruit cultivars in Tangará da Serra region, Mato Grosso State, Brazil at different evaluation times. The experiment was carried out with eight cultivars of yellow passion fruit from an ex situ germplasm bank of the State University of Mato Grosso. The floral resources (pollen and nectar) were evaluated in a completely randomized, factorial arrangement (8 cultivars x 5 evaluation times), with five replications. Throughout anthesis, the pollen viability, stigma receptivity, and sugar volume and concentration in the nectar were evaluated. The evaluations were carried out in 1-h intervals, between 1:30 and 5:30 p.m. The highest nectar volume production was at 2:30 p.m., decreasing gradually thereafter at the later evaluation times, for all cultivars. Pollen viability increased from the first to the second evaluation time and then decreased gradually until the last evaluation. Stigma receptivity was higher than 90% in all cultivars, at all evaluation times. BRS Rubi do Cerrado and FB 200 were the most promising cultivars for nectar volume and concentration, pollen viability, and stigma receptivity characteristics.